1975
DOI: 10.1080/00288233.1975.10421071
|View full text |Cite
|
Sign up to set email alerts
|

Starling (Sturnus vulgarisL.) predation on grass grub (Costelytra zealandica(White), Melolonthinae) populations in Canterbury

Abstract: The main stages of the grass grub's life cycle available to starlings are third-instal' larvae (autumn and winter) and adults (spring). Starlings were observed to concentrate their probing within localised areas of high grass grub density during autumn and winter, but the birds appeared to probe randomly for grubs within these areas. Average starling numbers were 1711.5-2915.4 starling-hours per ha per day during autumn and winter in 0.25-to 0.8-ha plots in an area of irrigated pastureland at Winchmore contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 96 publications
0
42
0
1
Order By: Relevance
“…The third assumption (that the vertical distribution of the grubs did not change between early and late April) is supported by the observations of East & Pottinger (1975), who found in 2 successive years at Winchmore that the proportion of grubs in the top 2.5 ern was stable from late March to early June. Our own samples from Field I showed that the grubs' vertical distribution did not change between late April and late May ( Table 2).…”
Section: Appendixmentioning
confidence: 76%
See 3 more Smart Citations
“…The third assumption (that the vertical distribution of the grubs did not change between early and late April) is supported by the observations of East & Pottinger (1975), who found in 2 successive years at Winchmore that the proportion of grubs in the top 2.5 ern was stable from late March to early June. Our own samples from Field I showed that the grubs' vertical distribution did not change between late April and late May ( Table 2).…”
Section: Appendixmentioning
confidence: 76%
“…1), some 15-20% less than that recorded in irrigated pastures in Canterbury (East & Pottinger 1975). The vertical distribution of the grubs was not influenced by density (Fig.…”
Section: Depth Of Soil Searched By Rooksmentioning
confidence: 77%
See 2 more Smart Citations
“…The first, an annual seasonal decline of aggregate numbers (Kain 1975), has been attributed to a combination of regulatory mechanisms including milky disease, rickettsia and other unspecified diseases (e. g. , Fowler 1974), protozoan infection (Miln et al 1979), predation (East 1972), and combat mortality (Kain 1975).…”
Section: Introductionmentioning
confidence: 99%